Psychological morbidity among female commercial sex workers with alcohol and drug abuse - Pandiyan, Kasthuri (Medknow Publications & Media Pvt Ltd, 2012)
INTRODUCTION: Substance abuse may act as precursors and also can form outcomes of sexual behaviors. The confluence of drug use, mental stressors, poverty, sexually transmitted diseases, low self-esteem and high-risk partners forms a fertile ground for psychological morbidity. AIM: To assess the psychological morbidity among female commercial sex workers (CSWs) who use alcohol and other substance abuse. MATERIALS AND METHODS: One hundred consecutive CSWs with alcohol and drug abuse patients attending the psychiatric OPD at Victoria hospital were assessed clinically. Relevant investigations were also carried out. General health questionnaire and substance use disorder identification tests were administered. RESULTS: A total of 100 cases between 30-40 years of age were taken up for the study. All were abusing alcohol with tobacco chewing or smoking being (64). Eighty-seven were married. Fifty of them being illiterate. Seventy-eight were suffering from physical illness. Two were HIV patient on treatment. Seventy-eight were having psychological morbidity (depression and adjustment disorder). CONCLUSION: Preventive interventions, targeting substance abuse and stimulating healthier-environments and providing economically independent.